Analisis Manajemen Rantai Pasok Komoditi Bawang Merah di Kebun Praktek Fakultas Teknologi Pangan Pertanian dan Perikanan Universitas Nusa Nipa - Regis, Fransiskus; Rato, Yoseph Yakob Da (Jurnal Ilmiah Wahana Pendidikan, 2024)
Supply Chain Management is a systematic approach to planning, controlling and managing the flow of goods, information and services from suppliers to end customers. It includes a number of interrelated stages in the journey of a product or service from production to consumption. The aim of this research is to determine the management of the shallot supply chain in the Unipa Practice Garden and the factors inhibiting the supply of shallots in the practice garden of the Faculty of Food, Agriculture and Fisheries Technology. The type of research used in this research is descriptive with a qualitative approach using data in the form of words, schemes and images. The sample used in this research were employees at the Unipa practice garden who were represented by the head of the practice garden with the consideration that the head of the practice garden knew all the activities that were taking place. The research results showed that: 1). Supply chain management in shallot farming involves at least 4 main actors. From the supply chain flow design, shallots are distributed from farmers to suppliers then distributed to retailers in local markets and then to final consumers. 2). The main inhibiting factors in the supply of shallots in the FTP3 Practice Garden are the supply of shallots from outside the city, limited market information, distribution not yet running well.